Introductory Surgical Skills Course: Technical Training and Preparation for the Surgical Environment - Sarah Miller; Edward Shipper; Brittany Hasty; Sylvia Bereknyei Merrell; Edmund W. Lee; Dana Lin; James N. Lau (Association of American Medical Colleges, 2018)
Introduction Early exposure to surgery in a positive learning environment can contribute to increased student interest. The primary objectives of this study included developing increased comfort in the operating room (OR) environment, confidence in surgical skills, and mentorship for students interested in surgery. Methods The course comprised seven 2-hour sessions covering both nontechnical and technical skills facilitated by attending and resident surgeons. Sessions included nontechnical skills training, basic knot tying and suturing, laparoscopic surgical skills, and high-fidelity operative simulations on animal and cadaver models. The curriculum also matched students with faculty mentors in order to scrub into operative cases. Surveys assessing self-reported comfort in the OR, confidence levels in surgical skills, and whether students had mentors in surgery were distributed before and after the course. Results Thirty preclinical medical students were enrolled in the course in 2016 and an additional 41 students in 2017. Results showed increased confidence in all skills and in comfort in the OR, as well as increased surgeon mentorship. Thirty-two students who completed the course entered clinical rotations in 2018 and, when surveyed, reported increased confidence in the aforementioned domains and in their preparedness for their surgery clerkship, compared to 49 peers who had not completed the course. Discussion The course successfully increased comfort in the OR, increased confidence in performing surgical skills, and provided students with mentors in surgery, all of which will hopefully foster positive experiences during their surgery clerkship and ultimately increase their consideration of surgery as a career.